Beginning volleyball - Jensen, Julie, 1957-; Jensen, Julie, 1957-; King, Andy (Minneapolis : Lerner Publications Co., 1995)
Shows basic techniques for beginning players of volleyball.
"Adapted from Fundamental volleyball.".
Includes bibliographical references (p. 62) and index.
Wilson's Children.
4.2
3-6
Keywords: Volleyball -- Juvenile literature; Volleyball; Volleyball